Modifikasi Metode Simple Additive Weighting Dalam Rekomendasi Restoran Terbaik Berdasarkan Ulasan Pengunjung - Prastowo, Kukuh Adi; Sulistiani, Heni; Setiawansyah, Setiawansyah (Forum Kerjasama Pendidikan Tinggi, 2024)
Simple Additive Weighting (SAW) is a method in DSS that is used to solve multi-criteria problems by adding up the value weights of each alternative. The weakness of SAW is its sensitivity to weight determination and value which can significantly affect the final result. If the weight or value of the criteria is not determined correctly or does not reflect reality well, the results of the decision can be less accurate. The purpose of this study is to modify the SAW method with the name SAW-C to be more effective in providing the best restaurant recommendations based on visitor reviews. SAW modification using a change driven approach not only improves accuracy in decision-making, but also improves adaptability and responsiveness to dynamic and complex environments. The SAW-C method not only improves decision-making accuracy, but also improves adaptability and responsiveness to dynamic and complex environments. SAW-C integrates flexibility and adaptability in managing changes in visitor preferences or the weighting of relevant criteria, which often change over time. With this approach, the recommendation system can dynamically update restaurant ratings based on recent reviews and changing visitor preferences, providing more personalized and relevant recommendations. The results of the ranking of the best restaurants using the SAW-C method show that the results of rank 1 with a final score of 0.92135 are obtained by Flamboyant Restaurant, rank 2 with a final score of 0.70548 obtained by Zozo Garden, and rank 3 with a final score of 0.70312 obtained by Square Restaurant.